ACM Digital Library (Association for Computing Machinery, 2001)
Provides bibliographic information, abstracts, reviews, and the full-text for articles published in ACM periodicals and proceedings since 1985 are available in the library together with works published by affiliated organizations. All material associated with an article is provided: bibliographic reference, index terms, abstracts, reviews, full-text.